Menjelajahi perkembangan pariwisata olahraga paralayang: Studi kasus perbandingan di Bali dan Jawa Tengah - Nur Afifah Indriyani; Agus Kristiyanto; Slamet Riyadi (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
One of Indonesia's top priorities still is tourism, which helps to boost regional development, employment, and the national economy. Among its developing sub-sectors, sport tourism, especially paragliding, has become increasingly popular because of Indonesia's varied and breathtaking natural surroundings. Still, differences in the evolution of tourism locations make it difficult to reach fair and sustainable tourism expansion. This paper attempts to investigate the main elements affecting the growth of paragliding sport tourism by means of a comparative case study of RIUG Paragliding in Bali and the Kemuning Paragliding Community in Central Java. Using a qualitative descriptive-comparative approach, the study thoroughly investigates tourism development strategies from several regional settings. Six key informants, three from each site who directly oversee tourist management, were used in a purposeful sampling process to gather data. Under the direction of the 4A tourism framework (Attractions, Accessibility, Amenities, and Ancillary Services), the study used in-depth interviews, structured observations, and document analysis. Data were transcribed, coded, categorized, and triangulated to guarantee validity and dependability. The results expose several methods of development: Whereas the Kemuning Paragliding Community stresses local resource use and volunteer involvement, RIUG Paragliding Bali uses a corporate-based model with contemporary facilities, integrated promotion methods, and stakeholder collaboration. The study comes to the conclusion that efficient development of paragliding sports tourism calls for cooperative governance involving corporate businesses, local communities, and government institutions to support sustainable and inclusive tourism expansion.